1988
DOI: 10.1016/0165-1781(88)90049-2
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline-induced supersensitivity of a central muscarinic mechanism: Lithium blocks Amitriptyline- induced supersensitivity

Abstract: Chronic treatment with amitriptyline produces dose-dependent super-sensitivity of a central muscarinic cholinergic mechanism involved in the regulation of core body temperature. The authors demonstrated that chronic treatment with lithium prevents the induction of this response. The potential clinical and theoretical significance of this finding is set forth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Thus, similar to the case for dopaminergic and β-adrenergic receptors, it has been suggested that lithium can block the development of cholinergic receptor supersensitivity. In behavioral studies, chronic lithium is reported to enhance some cholinergically mediated responses, including catalepsy and hypothermia (105,110)). Perhaps the most striking example of lithium's ability to potentiate muscarinic responses comes from the lithium-pilocarpine seizure model (111113).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Thus, similar to the case for dopaminergic and β-adrenergic receptors, it has been suggested that lithium can block the development of cholinergic receptor supersensitivity. In behavioral studies, chronic lithium is reported to enhance some cholinergically mediated responses, including catalepsy and hypothermia (105,110)). Perhaps the most striking example of lithium's ability to potentiate muscarinic responses comes from the lithium-pilocarpine seizure model (111113).…”
Section: Mechanism Of Actionmentioning
confidence: 99%